Proses Pengembangan Serai Wangi sebagai Minyak Alami serta Manajemen Limbah Pasca Produksinya di Desa Pendalian - Bellaaviska Bella; Desy Ria San Sitika; Doni Saputra; Hafizul Hanif; Hadi Purwanto (Jurnal Pengabdian UntukMu NegeRI, 2022)
Lemongrass is an herbal plant with the Latin name Andropogon nardus L. In Indonesia alone, lemongrass is widely cultivated. Not only as a flavoring in cooking, citronella is also a plant that produces atsiri oils. The chemical components contained in citronella are quite complex, but the most important are citronella and geraniol, as determinants of odor intensity, fragrance, and the value of the price of citronella oil. Not only the benefits of citronella can be taken, the waste from citronella can also be utilized. One area that produces citronella is Pendalian Village, Rokan IV Koto District, Rokan Hulu Regency, Riau. The owner of the garden directly carries out the production process and markets it to collectors, but since the COVID-19 pandemic, the price of citronella oil has dropped drastically and is difficult to market. The data collection method is carried out with partner site analysis and surveys. With this service, it is hoped that the owners of the lemongrass gardens in Pendalian Village can overcome the processing and marketing of citronella oil production, so that it can trigger the economic development of Pendalian Village.